DISPUTES IN THE APPLICATION OF EMPLOYMENT COPYRIGHT LAW RELATING TO THE PRINCIPLE OF STRICT LIABILITY IN ENVIRONMENTAL CLUSTERS - Mashudi, Mashudi; Basid, Abdul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
Numerous conflicts have arisen since the Omnibus Law-based Job Creation Law was passed, particularly in the environmental cluster. In this instance, it is evident in the environmental cluster of Article 22 Number 33 of the Job Creation Law, where the phrase